1996
DOI: 10.1111/j.1525-1446.1996.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clients Who Receive Home Health Aide Service

Abstract: Nurses who plan and supervise home health aide service must have a good understanding of the amount and intensity of nursing care and the amount of home health aide service that individual clients will need. However, there is little in the nursing literature that describes how clients who receive both RN and home health aide services differ from clients who receive only RN care. Indeed, there have been few reports on how need for home health aide service relates to the amount of nursing care received. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Fewer services were requested from the HHA. Only one third of the home care requests were for the combination of skilled nursing and home health aide visits, unlike prior research (Hayes & Willborn, 1996), which reported a greater proportion of home health aide usage.…”
Section: Discussioncontrasting
confidence: 69%
“…Fewer services were requested from the HHA. Only one third of the home care requests were for the combination of skilled nursing and home health aide visits, unlike prior research (Hayes & Willborn, 1996), which reported a greater proportion of home health aide usage.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, we examined the characteristics of elders who need home care services. The independent variables in the CHAID models are well‐known risk factors associated with the need for home help and home nursing (Choi et al, 2002; Goodlin et al, 2004; Guscia et al, 2006; Hays & Willborn, 1996). Therefore, the primary contribution of this study is the identification of elders who are most likely to need home care services.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research describes the factors that predict elders' need and use of home help and home nursing services (Choi et al, 2002; Goodlin et al, 2004; Guscia, Harries, Kirby, Nettelbeck, & Taplin, 2006; Hays & Willborn, 1996). However, none of these studies combined related factors to identify elders who are most likely to need home care services; hence, we could not anticipate service volume for a community.…”
Section: Research Questionsmentioning
confidence: 99%
“…The importance of services provided by nursing assistants in LTC facilities is widely recognized (Hays & Willborn 1996, Atchison 1998, Crogan & Shultz 2000). Similar to the US, nursing assistants play a major role in the operation of LTC facilities in Taiwan.…”
Section: Introductionmentioning
confidence: 99%